2020
DOI: 10.1021/acs.jcim.0c00006
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Sensitivity of Arginine Concentration to Preserve the Folded Form of Insulin Monomer under Thermal Stress

Abstract: Arginine, although popularly known as aggregation suppressor additive, has been found to quench proteins' structure and function by destabilizing their conformations. Driven by such controversial evidence, in this work we performed a series of atomistic molecular dynamics simulations of insulin monomer, a biologically active hormone protein, in arginine solution of varying concentrations (0.5, 1, and 2 M) at ambient and elevated temperature (400 K) to explore the arginine concentration driven structurebased st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 79 publications
0
24
0
Order By: Relevance
“…To probe the effect of varying pressure, temperature, pH, chemical modifications, and electric field on the structure of insulin, several MD studies were conducted ( 71 , 78 , 79 , 84 , 102 , 122 ). The effect of cations, various green solvents, and small molecules on the conformational stability of insulin was explored using several simulation studies ( 52 , 73 , 76 , 101 , 103 , 105 , 111 , 114 , 120 , 121 , 126 , 128 , 129 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To probe the effect of varying pressure, temperature, pH, chemical modifications, and electric field on the structure of insulin, several MD studies were conducted ( 71 , 78 , 79 , 84 , 102 , 122 ). The effect of cations, various green solvents, and small molecules on the conformational stability of insulin was explored using several simulation studies ( 52 , 73 , 76 , 101 , 103 , 105 , 111 , 114 , 120 , 121 , 126 , 128 , 129 ).…”
Section: Discussionmentioning
confidence: 99%
“…The binding of arginine stabilized the insulin dimer and hindered the transition to a hexameric state. Santra and Jana ( 126 ) reported a detailed study on the effect of arginine solution of varying concentrations (0.5M, 1M, and 2M) on the stability of the insulin monomer at near-physiological (300 K) and elevated (400 K) temperatures using atomistic MD and replica exchange MD (REMD) simulations. They revealed that the insulin monomer unfolds completely at 400 K in an aqueous medium, while in a 2M arginine solution the hormone maintains its native fold.…”
Section: Review Of Simulation Studies (1985 - To Date)mentioning
confidence: 99%
“…Majorly, two different classes of cosolvents, known as osmolytes (stabilizer) and denaturants, exist. Cosolvent-guided protein stability could be due to the solvation effects in which preferential exclusion of solvent from the protein surface occurs, thereby altering the hydration shell. However, the contribution of hydration was still observed to be important in preserving protein conformation in the presence of cosolvent.…”
Section: Introductionmentioning
confidence: 99%
“…Although plenty of experimental and computational studies established arginine as the protein aggregation suppressor to stabilize the native state of a protein, very little information on the role of arginine in stabilizing the folded native protein and inhibiting unfolding under thermal stress have been reported so far. In some recent studies, we investigated the interaction of insulin with different free amino acids in solutions. , Further, concentration-dependent osmolytic efficiency of arginine toward stabilizing the native folded form of insulin monomer was investigated . Among the tested solutions, 2 M arginine showed stabilizing behavior as compared to others.…”
Section: Introductionmentioning
confidence: 99%
“…To optimize the refolding of mutant R52Tat without EGFP, we compared the effect of an uncrowded environment on the TatR52A (purified) in E. coli cells with that of a crowded environment on EGFP in the absence of TAR RNA by BLI at 1.3 nm during a refolding period of 20 min ( Figures S4 and S5 ) [ 56 ]. We used this well-characterized system to assess the response of His-tagged Tat-BLI after binding to the TAR RNA substrate to design a BLI-detection study for mutant R52Tat folding without EGFP in the absence of TAR RNA ( Figure 5 and Figure S4 ) [ 3 , 57 ]. To normalize the refolding efficiency of the R52 mutant Tat, we monitored refolding buffer alone as a negative control.…”
Section: Resultsmentioning
confidence: 99%